Hubungan Antara Tingkat Pengetahuan dengan Tingkat Kepatuhan Penggunaan Obat Antihipertensi di Instalasi Rawat Jalan RS UNS: Jurnal Farmasi (Journal of Pharmacy), October 2025 - Ekawati, Oktavia; Hartono; Dian Anggraini, Truly (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2025)
Hypertension is still the largest disease in Central Java Province in the first quarter of 2023 at 63%. Various efforts to reduce mortality and morbidity due to hypertension have been carried out on a massive scale. The success of treating hypertension is influenced by a number of factors. An example of factors that have an impact is the patient's level of knowledge and understanding of hypertension and patient compliance in undergoing treatment. Knowledge and understanding are very necessary for patients to understand what to do and avoid so that treatment is successful. Compliance with hypertension treatment is important to monitor blood pressure and avoid complications. The research was conducted with the aim of determining the relationship between the level of knowledge and compliance with the use of antihypertensive drugs at UNS Sukoharjo Hospital. The study carried out was a cross-sectional type of research using a questionnaire. Compliance was measured using ARMS (Adherence to Refills and Medication Scale). The sampling technique used is purposive sampling which has inclusion provisions: patients who seek treatment in January-March 2024, undergo routine examinations. The number of samples that met the inclusion and exclusion requirements was 178 patients. Data analysis carried out the Spearman rank correlation test. The study findings show that patients who have a poor level of knowledge about hypertension and its treatment are 4.5%, a sufficient level of understanding is 28.1% and a good level of understanding is 67.4%. The level of patient compliance in using antihypertensive drugs in the low category was 62.4% and in the high category was 37.6%. The results of the Spearman rank correlation test obtained a p value of 0.000 (<0.05) which has a correlation value of 0.262. This indicates that there is a relationship with weak correlation strength on the level of knowledge and compliance in using antihypertensive drugs in the outpatient installation of UNS Sukoharjo Hospital.